Artifacts in Cone-Beam Computed Tomography of a Post and Core Restoration: A Case Report - Masoud Parirokh; Karim Ardjomand; Hamed Manochehrifar (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2012)
Abstract: Cone-beam computed tomography (CBCT) has been accepted as a useful tool for diagnosis and treatment in endodontics. Despite a growing trend toward using CBCT in endodontic practice the CBCT images should be interpreted carefully. This case report presents a case that showed radiolucency inside and around a tooth which was free of pathologic changes under a dental operative microscope and conventional radiographs. A male patient was referred to an endodontic office for evaluation of radiolucency inside and around tooth #21 in his CBCT images. The post and crown over the tooth was removed and the tooth was observed under a dental operative microscope. Clinical examination as well as direct observation under a dental operative microscope showed no pathological lesions inside and around the tooth. The misdiagnosis was based on an artifact on CBCT. Despite the advantages of CBCT images as a great radiographic aid in endodontic practice, in the presence of metallic structures such as post and core the images should be interpreted with caution.